Diseño y formulación del plan de calidad y documentación del componente estratégico de los requisitos de gestión de la ISO/IEC 17025:2005 para un laboratorio de ensayo (2009)
Testing laboratories, are implementing ISO 17025 for which technical requirements are the highest priority in order to deliver reliable results of the element to be analyzed. However to comply with the requirements related to the planning system and to overcome some obstacles related to the organizational culture itself of such organizations, this paper has set out five strategies to redirect the strategic approach of a laboratory test with general requirements of the standard, and with some activities to promote a culture of quality. As an innovator is a strategic proposal, which allows aligning the interests of the organization with the largest organization, generating value and guiding the management of them, in order to excellence.